Report on Evaluation of Rural Industries Projects - Planning Commission (Planning Commission, 1968)
Rural Industrial Projects constitute one of the significant efforts made for the utilisation of resources available in the rural area and removal of disparities in the development of different regions. The programme of rural industrialisation has also considerable potential for the utilisation of rural manpower and can be rated second only to the employment-oriented rural manpower projects. The programme had however faced problems pertaining inter-alia to supplies of raw material, entrepreneurial talent and marketing at the level of the industrial establishments. Similarly administrative and financial problems of a procedural nature exist at the project level. These problems need to be looked into and ironed out. This study was undertaken at the instance of the Rural Industries Planning Committee of the Planning Commission. The eight Rural Industries Projects for which case studios have been prepared wore selected in consultation with thorn. This report, along with the case studies, describes the working of these eight projects end throws up problems faced in their implementation. This report has boon prepared by the Economic Administration Division. I would like to thank the concerned State Governments and officers for the cooperation extended to our field officers in this work.
Programme Evaluation Organisation Planning Commission Government of India